Building bridges: Community-based projects for participation and social inclusion of rural NEETs - Tatiana Ferreira; Adriano Mauro Ellena; Frida Jonsson; Belém Barbosa; Pınar Uyan-Semerci; Emelj Tuna; Giedrė Kvieskienė; Elena Marta; İlkay Unay-Gailhard; Maria Fernandes-Jesus (NEETs in European rural areas: Individual features, support systems and policy measures, 2024)
This chapter focuses on factors that facilitate community-based projects for providing effective and sustainable responses to the challenges faced by young people Not in Employment, Education, or Training (NEETs) in rural areas and more specifically to promote their quality of life and social inclusion. In line with Bronfenbrenner's bioecological model (1977, 1979) and considering community-based projects as part of the exosystem, we aim to identify the barriers and constraints faced by projects targeting young NEETs in rural areas. As part of the collaborative research developed by the members of the “WG1—Rural NEETs Social Networks and Social Inclusion” of the Rural NEET Youth Network, we identified five promising community-based projects in Portugal, Italy, Sweden, North Macedonia, and Lithuania and conducted semi-structured interviews with the project coordinators. Our analysis showed that the identified projects take into account the different levels of the bioecological model and the need to involve how young people and local communities. Both these factors are crucial for their success and sustainability over time.
Keywords: 330; rural NEETs; youth inclusion; quality of life; participation; community-based projects